Quantification of Oxygen Consumption in Retina Ex Vivo Demonstrates Limited Reserve Capacity of Photoreceptor Mitochondria - Kooragayala, Keshav; Gotoh, Norimoto; Cogliati, Tiziana; Nellissery, Jacob; Kaden, Talia R.; French, Stephanie; Balaban, Robert; Li, Wei; Covian, Raul; Swaroop, Anand (Investigative ophthalmology & visual science, 2015)
Cell death in neurodegeneration occurs at the convergence of diverse metabolic pathways. In the retina, a common underlying mechanism involves mitochondrial dysfunction since photoreceptor homeostasis and survival are highly susceptible to altered aerobic energy metabolism. We sought to develop an assay to directly measure oxygen consumption in intact retina with the goal of identifying alterations in respiration during photoreceptor dysfunction and degeneration. Circular punches of freshly isolated mouse retina, adjacent to the optic nerve head, were used in the microplate-based Seahorse Extracellular Flux Analyzer to measure oxygen consumption. Tissue integrity was evaluated by propidium iodide staining and live imaging. Different substrates were tested for mitochondrial respiration. Basal and maximal respiration were expressed as oxygen consumption rate (OCR) and respectively measured in Ames' medium before and after the addition of mitochondrial uncoupler, BAM15. We show that glucose is an essential substrate for retinal mitochondria. At baseline, mitochondria respiration in the intact wild-type retina was close to maximal, with limited reserve capacity. Similar OCR and limited mitochondrial reserve capacity was also observed in cone-only Nrl-/- retina. However, the retina of Pde6brd1/rd1, Cep290rd16/rd16 and Rpgrip1-/- mice, all with dysfunctional or no photoreceptors, had reduced OCR and higher mitochondrial reserve capacity. We have optimized a method to directly measure oxygen consumption in acutely isolated, ex vivo mouse retina and demonstrate that photoreceptors have low mitochondrial reserve capacity. Our data provide a plausible explanation for the high vulnerability of photoreceptors to altered energy homeostasis caused by mutations or metabolic challenges.